ОРГАНИЗАЦИЯ ИССЛЕДОВАТЕЛЬСКОЙ ДЕЯТЕЛЬНОСТИ ДЕТЕЙ СТАРШЕГО ДОШКОЛЬНОГО ВОЗРАСТА ДЛЯ ПОВЫШЕНИЯ ЭКОЛОГИЧЕСКОЙ КУЛЬТУРЫ - Адамова Л. К.; Нектегаева Н. К. (World Science, 2019)
Environmental education is one of the urgent problems of our time. Educational and research activities contribute to the formation of environmental culture of children, the formation of a holistic picture of the world preschooler and the foundations of cultural knowledge of the world around them.